Effects of pepper extract in suckling lamb feed: growth performance, metabolism, and oxidative responses - De Oliveia Cecere B.G.* (2022)
© 2022 Bruno Giorgio de Oliveia Cécere et al., published by Sciendo.Our objective was to determine whether the inclusion of pepper extract would improve health in suckling lambs, stimulating antioxidant activity, and improving performance. We used Lacaune lambs distributed in four treatments, with four repetitions per treatment and three lambs per repetition: control group (T0) and treatments T1, T2, and T3 that received 200, 400, and 800 mg/kg of pepper extract, respectively. Groups T1 and T2 consumed more significant amounts of silage than group T0, and animals from group T1 consumed more concentrate and, consequently, consumed more solids. The addition of pepper extract enhanced growth performance, with the lowest dose (T1) giving rise to the most significant weight gain, average daily gain, and body weight, compared to T0. Regression analysis showed that the optimum point for pepper extract supplementation was 301.5 mg/kg. The levels of total protein and globulins were significantly higher for animals supplemented with pepper extract (day 28) than the control; the concentrations of albumin and urea increased over time but did not differ significantly among treatments. Serum glucose levels decreased significantly over time; however, the groups supplemented with pepper extract showed higher concentrations than group T0. The hematocrit was significantly higher in groups fed pepper extract; hemoglobin concentrations were also more significant, increasing over time in both groups. The groups that consumed the pepper extract had higher leukocyte counts due to greater lymphocytes and neutrophils. Levels of non-protein thiols increased significantly over time, while lipid peroxidation levels decreased significantly in all groups. The concentrations of reactive oxygen species significantly decreased in the serum of group T3 animals, those fed with pepper extract (day 28), compared to the control. In general, the addition of pepper extract in lamb feed can enhance weight gain, increase antioxidant levels, and stimulate the production of leukocytes and globulins in lambs.